Challenging the Comparison in Montgomery Between Patients and 'Consumers Exercising Choices'. (9th September 2021) - Jackson, Emily
Abstract: In Montgomery v Lanarkshire Health Board, Lords Kerr and Reed referred to the increasing tendency to treat patients 'as consumers exercising choices'. The question of whether it is helpful to regard patients as consumers is not a new one, but it arises most frequently in discussions about the commercialisation of healthcare. Comparing patients with consumers in relation to informed consent is an interesting development, especially in the light of the growing body of contract and consumer law scholarship which questions the extent to which information disclosures to consumers produce informed choices. If there is evidence that the duties of disclosure which are imposed on retailers, in order to redress the imbalance of knowledge and power in the consumer–retailer relationship, do not always fulfil their intended purpose, might this have any resonance for the duties of disclosure which are imposed upon healthcare professionals?